Projetos sociais desenvolvidos em universidades da cidade de São Paulo: mapeamento e análise - Vercelli, Ligia de Carvalho Abões (2012)
The present work has the aim to analize four social projects, two of them developed at Universidade Nove de Julho UNINOVE projects Reading and Wrinting and Legal Practice (NPJ) and two at Pontifícia Universidade Católica de São Paulo PUC-SP projects Interdisciplinarity Educacion of Youngsters and Adults and Office Model Dom Paulo Evaristo Arns , with the goal to investigate if they practice actions of social commitment or social rasponsability. The formes search to provoke alterations in culture and world view of the students and people who use them, the second finish their aim practicing services to the community. As metodological phases we, first of all, researched through theorical and bibliographical sources, analysing seven categories: Social Responsibility, Academic Social Commitment, Social Projects, Social Inclusion/Exclusion, Citizenship, Social Recognizement and No Formal Education. The second metodological phase was the accomplishment of field research in which was used semi-structued research, whit the following subjects: four are coordinatores of the mentioned projects, the sociologist and psychologist of Office Model, da PUC_SP, twenty two students and twenty four users. After the speeches analyses and the subjects, we concluded that the projects Reading and Writing from UNINOVE and Interdisciplinarity Educacion of Youngsters and Adults from PUC-SP are actions of social commitment. The Legal Practice of UNINOVE has its characteristic as an action of social responsibility, because its aim has an end during the serveces practiced toward the community. The Office Model Dom Paulo Evaristo Arns , from PUC-SP, about the individual actions, we mean, contendious, at present is represented as an action of social responsibility, prowever it goes directly to the social commitment and inversely the common actions consolidate themselves as social commitment.